Ascites Associated with Ancylostomiasis in Dogs - Rao, Neha; Sadhu, Dashrath B.; Shah, Aditya I.; Parmar, Jignesh J.; Patel, Deepak M. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
Ascites is the accumulation of fluid in the abdominal cavity. It is a common presenting condition with diverse formsof etiologies. Ascites manifest in several disease conditions such as nephrotic syndrome, congestive heart failure, rightside heart failure, chronic liver failure, portal hypertension, kidney failure, malnutrition, hypoalbuminemia, lymphoma,peritonitis, hookworm infection (Peden and Zenoble, 1982; Randhawa et al., 1988).